The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1016/j.ensci.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and influence of chronic obstructive pulmonary disease on stroke outcomes in hospitalized stroke patients

Abstract: BACKGROUND Chronic obstructive pulmonary disease (COPD) and stroke are important causes of death. COPD patients are at higher risk of cerebral hypoxia and aspiration. Yet, relatively little is known about the prevalence of COPD among stroke patients or its impact on outcomes after an index stroke. We assess the prevalence of COPD among hospitalized stroke patients in a nationally representative sample and examine the effect of COPD with mortality risk in the hospital after a stroke. METHODS Using the Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 23 publications
1
29
3
Order By: Relevance
“…This study shows that the presence of COPD is an independent risk factor for early mortality in stroke patients. 85…”
Section: Primary Studiesmentioning
confidence: 99%
“…This study shows that the presence of COPD is an independent risk factor for early mortality in stroke patients. 85…”
Section: Primary Studiesmentioning
confidence: 99%
“…[7] Only one observational study has addressed the association between COPD and mortality in patients with SAH. [8] That study demonstrated that COPD did not increased mortality. However, that study did not control for important confounders, such as severity of disease, smoking, or medical history.…”
Section: Introductionmentioning
confidence: 92%
“…With the increasing global incidence of COPD [13] and its high prevalence in patient with aSAH [8], we assessed the impact of COPD on outcomes of in patients with aSAH, using propensity score matching (PSM) to form groups for comparison with near-identical distributions of background and potential confounder variables.…”
Section: Introductionmentioning
confidence: 99%
“…On multivariable analyses, COPD is modestly associated with overall stroke mortality (OR 1.06; 95% CI 1.02-1.08; p=0.018) but it is strongly associated with higher mortality among patients with intracerebral hemorrhage (OR 1.12; 95% CI 1.03-1.20; p=0.005) and ischemic stroke (OR 1.08; 95% CI 1.03-1.13, p=0.001). However, no excess mortality was 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 observed among COPD patients when the analysis was restricted to ischemic stroke patients who received recombinant tissue plasminogen factor (10).…”
Section: Impact Of Copd On Stroke Outcomesmentioning
confidence: 98%
“…It has been demonstrated that there is a tight interplay between COPD, acute and chronic cardiovascular disease. (7)(8)(9) But it has also been suggested that COPD is significantly more prevalent among patients with stroke and that the co-existence of both is associated with grim outcomes (10). These findings have been consistently observed in studies evaluating all different subtypes of stroke (ischaemic, intracerebral or subarachnoid hemorrhage) (11).…”
mentioning
confidence: 95%